AN AYURVEDIC MANAGEMENT OF EKAKUSHTHA (PSORIASIS VULGARIS) THROUGH VIRECHANA KARMA (PURGATION THERAPY) AND SHAMANA CHIKITSA (PALLIATIVE THERAPY): A CASE STUDY - Govind Kumar Verma; Niharika Shakya; Harish Bhakuni; Deepti Bhakuni; Ram Kishor Joshi (International Journal of Ayurveda and Pharma Research, 2020)
A 21 years old female patient had complained of silvery scaly skin lesions all over body with reddish discoloration having severe itching, burning sensation since 15 years back that got aggravated during each rainy and cold season. Examination- 1. Severe silvery scaly lesions shaded down on rubbing all over the day, 2. Characterized by sharply demarcated and erythematous papulosquamous lesions (Dry, thin, silvery-white scales), 3. Irregular, discoid and oval in shape. 3. Small areas of bleeding where the involved skin is scratched, 4. Scaly plaques on the scalp, 5. Auspitz Sign-positive, 6. Candle grease sign-Positive, 7. Grattage Test-Positive. Aims and Objectives: To prove the role & efficacy of Virechana drugs, Virechana Karma, Sansarjana Karma & Sanshamana chikitsa. Materials and Methods: 1. Dadimashtaka Choorna was given 5gm twice a day with lukewarm water continuously for 3 days as Aama Dosha Pachanartha, 2.Guggulutiktakaghritama was given 25ml, 50ml, 75ml, 100ml, 125ml, 150ml & 200ml with lukewarm water for next 7 days as Snehana Karma, 3. Bahya Snehana with Dashamoola Taila and Bahya Sarvaanga Swedana with Dashmoola Kwatha were applied for next 3 days, 4.Virechana Karma was done after Samyaka Snehana & Swedana. 5. Sansarjana Karma was done after Samayaka Virechana for 7 days. Differential Diagosis-Sidddham, Mandalkushtha & Ekakushtha. Provisional Dignosis-Ekakushtha, Final Diagnosis-Ekakushtha (Psoriasis vulgaris). Result: Significantly improvements were observed in treatment of Ekakushtha (Psoriasis vulgaris). Discussion: Deepana & Pachana chikitsa is responsible for Aama Dosha Pachanartha. Snehana is responsible for Srotosamamardawama. Swedana is responsible for Srotomargavishodhanam. Virechana is responsible for pacifying vitiated Pittaja as well as Kaphaja Dosha and Vyadhi.